The Battle for the Soul of Capitalism - John C. Bogle (USA Yale University Press, 2005)
There is no one better qualified to tell us about the failures of the American financial system and the grotesque abuses that have taken place in recent years than John Bogle, who as founder and former chief executive of the Vanguard mutual funds group has seen firsthand the innermost workings of the financial industry. A zealous advocate for the small investor for more than fifty years, Bogle has championed the restoration of integrity in industry practices. As an astute observer and commentator, he knows that a trustworthy business and financial complex is essential to America's continuing leadership in the world and to social and economic progress at home. This book tells not just a story about what went wrong but, more important, the story of why we lost our way and of how we can right our course. Bogle argues for a return to a governance structure in which owners' capital that has been put at risk is used in their interests rather than in the interests of corporate and financial managers. Given that ownership is now consolidated in the hands of relatively few large mutual and pension funds, the specific reforms Bogle details in this book are essential as well as practical. Every investor, analyst, Wall-Streeter, policy maker, and businessperson should read this deeply informed book.
Keywords: Business; Economics; Finance; Nonfiction; Politics; Corporations; Mutual funds; Capitalism; Investments; Global Citizenship (BIN1064-N)